The impact of maternal post‐partum depressive symptoms on child diet at 18 months - Rachelle S. Opie; Miaobing Zheng; Susan Torres; Karen Campbell (Wiley, 2021)
Abstract Post‐partum depression (PPD) is a serious mental health problem, which can impair maternal behaviours and adversely affect the cognitive, emotional and behavioural development of children. This study aims to explore the impact of maternal depressive symptoms at 3 months post‐partum (baseline) on child diet at 18 months of age (follow‐up). This study used longitudinal data from 263 first‐time mothers from the Melbourne Infant Feeding, Activity and Nutrition Trial (InFANT) Extend. Women self‐reported depressive symptoms (10‐item Center for Epidemiological Studies Depression Scale [CES‐D]) and child diet (fruits, vegetables and discretionary foods). Multiple linear regression analyses were used to explore the relationship between maternal depressive symptoms at baseline and child fruit and vegetable intake and discretionary food intake (g day−1) at follow‐up. Baseline maternal depressive symptoms were associated with higher childhood consumption of discretionary foods at 18 months of age (β = 0.45, 95% confidence interval [CI] 0.03 to 0.87, P = 0.034 [adjusted]). There was no evidence of association for maternal depressive symptoms and child intake of fruits and vegetables. Further longitudinal studies are warranted to confirm these findings, with the hope of translating this knowledge into optimal clinic care and improved physical and mental health for mother and child.